2022
DOI: 10.1111/1440-1681.13675
|View full text |Cite
|
Sign up to set email alerts
|

Rovatirelin ameliorates motor dysfunction in the cytosine arabinoside‐induced rat model of spinocerebellar degeneration via acetylcholine and dopamine neurotransmission

Abstract: Thyrotropin-releasing hormone (TRH) and the TRH mimetic taltirelin have been used in Japan for the treatment of spinocerebellar degeneration (SCD), a type of progressive ataxia. A TRH mimetic, rovatirelin, ameliorates ataxia symptoms in the rolling mouse Nagoya, a hereditary SCD model. The aim of this study was to verify the effects of oral administration of rovatirelin on a cytosine arabinoside (Ara-C)-induced ataxia rat model, a sporadic SCD model characterized by gait abnormalities and falls because of cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Further, Ijiro et al ( Ijiro et al, 2020 ) found that in spinocerebellar ataxia (SCA) model animals, rovatirelin, which activates the cerebellum and other parts of the central nervous system to improve motor function, is more effective than taltirelin. Rovatirelin also improve motor dysfunction in a cytarabine-induced rat model of spinocerebellar degeneration (SCD) via acetylcholine and dopamine neurotransmitters ( Ijiro et al, 2022 ). It follows that rovatirelin may have orally effective therapeutic potential for patients with SCD and SCA ( Table 3 ).…”
Section: Thyrotropin Releasing Hormone Receptormentioning
confidence: 99%
“…Further, Ijiro et al ( Ijiro et al, 2020 ) found that in spinocerebellar ataxia (SCA) model animals, rovatirelin, which activates the cerebellum and other parts of the central nervous system to improve motor function, is more effective than taltirelin. Rovatirelin also improve motor dysfunction in a cytarabine-induced rat model of spinocerebellar degeneration (SCD) via acetylcholine and dopamine neurotransmitters ( Ijiro et al, 2022 ). It follows that rovatirelin may have orally effective therapeutic potential for patients with SCD and SCA ( Table 3 ).…”
Section: Thyrotropin Releasing Hormone Receptormentioning
confidence: 99%
“…TRH mimetics have been shown to be useful in the treatment of spinocerebellar degeneration ( Shimizu et al, 2020 ; Ijiro et al, 2022 ), amyotrophic lateral sclerosis ( Hawley et al, 1987 ), spinal muscular atrophy ( Kat o et al, 2009 ), prolonged disturbance of consciousness due to aneurysmal subarachnoid hemorrhage ( Shibata et al, 2019 ), Parkinson’s disease ( Zheng et al, 2018a ; Zheng et al, 2018b ), epilepsy ( Rajput et al, 2009 ; Sah et al, 2011 ), psychiatric disorders with underlying inflammatory processes ( Kamath, 2012 ), and possibly depression ( Duval et al, 2021 ). The effects of TRH and its analogs on the CNS are usually achieved in cooperation with the modulatory effects of neurotransmitters such as glutamate, dopamine, norepinephrine, acetylcholine, serotonin, or GABA.…”
Section: Thyrotropin-releasing Hormone Receptor Ligands and Their Pha...mentioning
confidence: 99%